Impact of Video Technology for Improving Success of Medial Canthus Episcleral Anesthesia in Ophthalmology. Issue 6 (1st November 2017) - Guerrier, Gilles; Rothschild, Pierre-Raphaël; Lehmann, Mathieu; Azan, Frédéric; Baillard, Christophe
Abstract : Background and Objectives: Efficient learning of regional anesthesia in ophthalmology remains challenging because trainees are afforded limited opportunity to practice ocular anesthesia. The aim of this prospective, randomized, blinded study was to determine whether teaching with video improves regional anesthesia skills of residents in ophthalmology. Methods: From January to October 2016, 32 novice anesthesiology residents were evaluated while performing medial canthus episcleral procedures during a 5-day rotation. Residents were randomly assigned to either receive or not receive a video review of their performance at day 3. The primary outcome was a comparison of akinesia using a 12-point scale before incision assessed by the blinded surgeon. Results: A total of 288 blocks were performed by 32 residents and were assessed by 3 surgeons before the intervention (144 blocks) and after the intervention (144 blocks). Residents in the review group improved to a greater degree compared with residents in the no-review group. The median overall akinesia scores for the review and no-review groups were similarly low (6; interquartile range [IQR], 2–11; and 6 [IQR, 2–9], respectively) on day 1 of the rotation, whereas anesthesia performed by residents in the video group provided a better akinesia score (12 [IQR, 10–12] vs 8 [IQR, 6–10]; P < 0.001) on day 5 of the rotation. Conclusions: Video-assisted teaching significantly improves performance of medial canthus episcleral anesthesia performed by novice trainees.